Perancangan Sistem Informasi Praktek Kerja Industri (Prakerin) Pada SMK Negeri 1 Kota Serang - Intan, Tifani; Fatullah, Rizki; Gunawan, Rudi (Teknik Informatika Fakultas Ilmu Komputer, 2022)
Industrial work practice or prakerin is an activity carried out by every vocational school student in Class XI. This activity is an implementation of the science of vocational students in the world of work, in addition to being an experience for students when graduating from school. SMK Negeri 1 Serang is one of the schools organizing this activity and the Industrial Relations section is the party that handles prakerin activities. Industrial Relations Department (hubin), handles prakerin activities ranging from finding prakerin places and cooperating with agencies, to monitoring students during prakerin and archiving documents related to prakerin. In this activity, the homeroom teacher is involved in delivering practical information to students in the classroom. Based on the problems found, hubin has difficulties in the placement of prakerin students. In addition, the monitoring process still found obstacles sourced from agencies, as well as document management related to prakerin is still done manually, and making it difficult to see when the data is needed. Some of these problems implement prakerin to be less than the maximum, therefore the author will make the design of Information Systems based prakerin using the waterfall method as a method of system development. System modeling using the unified modeling language (UML), as well as the design of the system view that will provide an overview of the system created. The expectation of the design of the industrial work practice information system (prakerin) web-based is to assist the industrial relations (hubin) in the implementation of prakerin activities at SMK Negeri 1 Serang City.